Criteria affecting the audience numbers in performing art organizations - Smolny, Katarzyna; Gałecka, Małgorzata (Kryteria wpływające na poziom liczby widzów w instytucjach wystawiennicznych, 2019)
The problem is finding the optimal and efficient model of public funding. The development of an objective theatre funding model is a major challenge for both the entities developing as well implementing the cultural policy. The aim of this article is to identify the criteria/measures having the potential effect on the increase of the audience numbers in individual theatres in Poland. This aim is implemented using Multi Criteria Decision Making (MCDM), the result of which is to achieve full distribution of a set of variants (individual theatres) in accordance with the monitored criteria (audience numbers in a theatre). Our research found the important role of both financial and non-financial indicators among which technical indicators are essential. On this basis, the need to develop optimal allocation of public funds between theatres in terms of their technical capabilities or infrastructure should be considered
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 96-113